2003
DOI: 10.1139/w03-065
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of hepatitis C virus infection in hemodialysis patients by monthly analysis of HCV RNA and antibodies

Abstract: The aims of this study were to (i) evaluate the prevalence and the incidence of hepatitis C virus (HCV) infection in hemodialysis patients in two different centers in São Paulo (Brazil), (ii) determine the time required to detect HCV infection among these patients by serology or PCR, (iii) establish the importance of alanine aminotransferase determination as a marker of HCV infection, and (iv) identify the HCV genotypes in this population. Serum samples were collected monthly for 1 year from 281 patients admit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
25
3
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 17 publications
(12 reference statements)
5
25
3
5
Order By: Relevance
“…However, the predominance of genotype 1, subtype 1a was also found in other Brazilian studies carried out among hemodialysis patients 1,8,10,15,16,19,23 . These data suggest that the high frequency of subtype 1a is probably a consequence of HCV nosocomial transmission in hemodialysis units.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…However, the predominance of genotype 1, subtype 1a was also found in other Brazilian studies carried out among hemodialysis patients 1,8,10,15,16,19,23 . These data suggest that the high frequency of subtype 1a is probably a consequence of HCV nosocomial transmission in hemodialysis units.…”
Section: Resultssupporting
confidence: 69%
“…Studies carried out in São Paulo 15,16,19 , Rio de Janeiro 3 , Belo Horizonte 7 , Recife 1 , Tocantins 23 , Goiás 8 and Campo Grande 10 have shown that genotype 1, subtype 1a, was prevalent in those patients. However, the genotyping methods employed in the majority of those studies (except in Goiás State), which were based on 5' NC region analyses, did not permit the correct identification of the HCV subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreira [39], in a prospective study, observed a 14.6% prevalence of HCV infection and an incidence of 3.1/1000 affected individuals/month, in an analysis of chronic renal patients from two dialysis centers in the metropolitan region of São Paulo, Brazil. Simmonds [40], using ELISA and 2 nd generation IB tests, performed antibody detection on 217 patients undergoing hemodialysis.…”
mentioning
confidence: 99%
“…Moreira [39] observed that the monthly determination of ALT does not aid in the early detection of HCV infection. The values that were observed were within the normal upper limit for ALT in both carrier patients and non-carrier patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation